The Role of Values in Preservice Teachers' Decision to Teach. Issue 1 (2nd January 2017) - Torsney, Benjamin M.; Ponnock, Annette R.; Lombardi, Doug
ABSTRACT: The current study explored the values preservice teachers use as motivation for pursuing a teaching career. Preservice teachers ( N = 97) from a large Northeastern urban university were chosen to complete a survey measuring personal utility value, social utility value, and epistemic value. Data analysis was conducted using exploratory factor analysis, correlations, multivariate analysis of variance (MANOVA), and multivariate analysis of covariance (MANCOVA). Results indicated moderate and significant correlations among subscales; a two-group MANOVA demonstrated that females were rated higher on the subscale desire to work with children/adolescents and Secondary Education participants rated highest on social contribution ; and a MANCOVA using sex as the covariate demonstrated that participants pursuing Early Childhood Education were rated higher on the personal utility value main scale and the time for family and job transferability subscales.